Covert Criminalization of LGBT Individuals: A Juridical Analysis of Court Decisions Based on the Pornography Law and the Criminal Code from a Critical Legal Studies Perspective - Maharani Roesiana Maaturwey (Media Hukum Indonesia (MHI), 2026)
This study analyzes the phenomenon of covert criminalization against LGBT individuals in Indonesia through court decisions based on the Pornography Law and the Criminal Code. Although Indonesian law does not explicitly criminalize sexual orientation, law enforcement practices often rely on morality-based provisions to prosecute individuals associated with LGBT identities. Using a normative juridical approach and a case analysis method, this research examines how judges interpret and apply these legal norms. By applying the Critical Legal Studies perspective, this study finds that such legal practices indicate an expansion of normative interpretation influenced by social and moral pressures. This raises concerns regarding legal certainty, equality before the law, and the protection of minority rights. The study highlights the gap between law in books and law in action in the Indonesian legal system.